Aerodynamic effects of propulsion integration for high bypass ratio engines - Stankowski, Tomasz; MacManus, David G.; Robinson, Matthew; Sheaf, Christopher T. (American Institute of Aeronautics and Astronautics (AIAA), 2017)
This work describes the assessment of the effect of engine installation parameters such as engine position, size, and power setting on the performance of a typical 300-seater aircraft at cruise condition. Two engines with very high bypass ratio and with different fan diameters and specific thrusts are initially simulated in isolation to determine the thrust and drag forces for an isolated configuration. The two engines are then assessed in an engine–airframe configuration to determine the sensitivity of the overall installation penalty to the vertical and axial engine location. The breakdown of the interference force is investigated to determine the aerodynamic origins of beneficial or penalizing forces. To complete the cruise study, a range of engine power settings is considered to determine the installation penalty at different phases of cruise. This work concludes with the preliminary assessment of cruise fuel burn for two engines. For the baseline engine, across the range of installed positions, the resultant thrust requirement varies by 1.7% of standard net thrust. The larger engine is less sensitive with a variation of 1.3%. For an assessment over a 10,000 km cruise flight, the overall effect of the lower specific thrust engine shows that the cycle benefits of −5.8% −5.8% in specific fuel consumption are supplemented by a relatively beneficial aerodynamic installation effect but offset by the additional weight to give a −4.8% −4.8% fuel-burn reduction.